Lietuvos valdovo Vytauto titulatūra: kada Vytautas ima tituluotis Didžiuoju kunigaikščiu? - Skurvydaitė, Loreta (Lietuvos istorijos studijos, 2000)
Lithuanian ruler until the Krėva union used to have different titles. Although, in a variety of names, the title of the Lithuanian ruler was superior to those of the ruling dynasty. As a consequence of the Krėva union, the title of the Lithuanian ruler was being formed in a framework of two poles: on one side it was the title of Jogaila as the king of Poland, and on the other side, it was the title of Vytautas - a local and later an independent ruler of Lithuania.When Jogaila became the king of Poland, the Lithuanian title of the Lithuanian ruler was combined with that of the Polish king. The formation of the title belonging to the local Lithuanian ruler Vytautas was closely related to the title of patrimonial Lithuanian ruler - Jogaila.The first titles defined Vytautas as a local duke ruling over some territories. Under the Astrava treaty, Vytautas became Jogaila's vicegerent in Lithuania. However, on conducting local affairs he did not avoid titling himself as a grand duke of Lithuania in Russian documents. With an increase of his power, Vytautas transferred this title of grand duke to German documents. The relationships with the Orden represent only a very narrow channel with the outside world. At that time the international language was Latin. It was a high-rank diplomatic language. Thus, the Latin document of 1396, where Vytautas titled himself as the grand duke, is of very great importance. With reference to this, we can assume that Vytautas titled himself officially for the first time as the grand duke of Lithuania. Up to 1396, Vytautas was in conformity with the Astrava treaty representing himself as a vicegerent, but from 1396 he stepped over the limits of this treaty.